Bernard Plossu : une nouvelle mythologie familiale - Tisseron, Serge (CV Photo)

(untitled) (Les Productions Ciel variable, 1999)
Summary As we all know, the family is in crisis. Like a company that is running out of steam, it needs images to exalt its specificity. It is indisputable that affection forms the fabric of family life -a fabric that characteristically stretches over several generations. It contributes to the undefinable sense of calm safety and shared emotion that is not only the best the family has to offer - although it does not always do so - but is the thing that it alone can offer. Bernard Plossu offers us an aestheticization of this family affection at a moment when it is perhaps not in a crisis of existence, but definitely in a crisis of representation. Plossu offers representations of the family that follow the daily experiences we all have with our loved ones: kissing, caressing, sleeping together. His images develop from concrete, innocuous situations whose value is solely in the feelings and emotions shared within them, and in them we can all dream of recognizing ourselves and our loved ones.